Use Of Copper Smelting Stones in The Production of Filler Mixtures - Abdurakhimov Abdukarim Abdukhalimzoda (Zien Journals, 2021)
This article is devoted to the optimization of the use of industrial wastes, chemical and mineral additives in the deposits of fillers in the country, to improve the properties of fillers. mineral cotton, pavement concretes, alloys for filling mountain cavities and other construction materials.
Keywords: Filler; mineral; industrial; waste